Useful & Reliable: Technological Transformation in Colonial India - Roy, Tirthankar (Technology and culture, 2021)
The proposition that Useful and Reliable Knowledge (URK) produced divergent patterns of long-term economic growth implies that such knowledge had weak agency in countries that fell behind. This article rejects such a theory on the evidence of colonial India. Indo-European contacts activated transfer, transplantation, and adaptation in URK; however, the impact was uneven within India. Despite boosting productivity in manufacturing and consumption, large areas were left untouched. These contrasts highlight the differentiated impact of URK on production conditions in India and question its transferability and mode of knowledge exchange under colonialism.